Implementation of Active Learning Tools in Modern Pedagogy - Prabhavalikar, Aniket A.; Patil, Mahadev S. (Journal of Engineering Education Transformations, 2022)
Now-a-days, it is important to integrate innovative tools in engineering education. It is need of hour that conventional teaching-learning techniques should be replaced by state-of-art tools that enable instructor to deliver the content in effective manner so that learners become proactive in teaching-learning process. Active learning tools play a vital role in modern day pedagogy. Today’s pedagogical tools in active learning give that opportunity to learners to exercise their problem-solving skills and allow them to work collaboratively in groups. A detailed analysis of tools such as Kahoot, Eclipse crossword and flipped class is discussed in this paper. Our analysis involved engineering learners from Electrical and Electronics and Communication streams from our college. Participation of learners in activities such as Kahoot and Eclipse crossword was more compared to flipped class which indicates learners are more inclined towards puzzle solving and quizzing technique. We examined how these techniques improved students’ approach towards learning. It is a prime duty of instructor to engage students in the activities which serves the purpose of learning by doing. Active learning tools play critical role in making students proactive in their learning phase.